Eye Movements and Visual Cognition - Klein, Raymond M.; Liversedge, Simon P. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This eBook is a volume based on the "Eye Movements and Visual Cognition" Special Issue published in the journal Vision by MDPI and edited by Raymond Klein and Simon Liversedge. The eBook comprises 19 high-quality chapters that are original and topical works by leading academic figures in the field of human vision and visual cognition. In putting together the book, we aimed to provide an informative body of work to stimulate and foster useful intellectual exchange between individuals working on basic theoretical issues as well as on more applied aspects of vision and cognitive science. From the outset, we sought papers that provide concise and astute reviews of topics within this broad field. The present volume includes reviews that are narrative (critiquing and summarizing research on a topic), tutorial (with a focus on methods and findings), empirical (e.g., meta-analytic), and theoretically synthetic. The eBook also features chapters with new empirical content that resolves an undecided issue stemming from an evaluation of the literature. Finally, where possible, we also selected papers that bridge theoretical and applied issues and provide insight into behavior and its neural substrate. All chapters were subject to peer review and went through several rounds of revision prior to acceptance.